2022
DOI: 10.3390/microorganisms10020291
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Queensland Fruit Fly Microbiome through the Transition from Nature to an Established Laboratory Colony

Abstract: The transition from nature to laboratory or mass rearing can impose significant physiological and evolutionary impact on insects. The Queensland fruit fly (also known as ‘Qfly’), Bactrocera tryoni (Froggatt) (Diptera: Tephritidae), is a serious economic pest that presents major challenges for horticulture industries in Australia. The sterile insect technique (SIT) is being developed to manage outbreaks in regions that remain free of Qfly and to suppress populations in regions where this species is endemic. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…Moreover, changes in the larval microbiome due to captivity can occur in even relatively short periods. Majumder et al (2022), for example, already detected changes in larval microbiomes after a single generation in captivity. Interestingly, changes in the adult microbiome took more generations before they started to occur.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, changes in the larval microbiome due to captivity can occur in even relatively short periods. Majumder et al (2022), for example, already detected changes in larval microbiomes after a single generation in captivity. Interestingly, changes in the adult microbiome took more generations before they started to occur.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was in line with previous studies performed on C. capitata populations (Aharon et al, 2013 ; Malacrinò et al, 2018 ). To the best of our knowledge, the effect of laboratory adaptation was investigated only in two tephritid flies: Anastrepha fraterculus (Salgueiro et al, 2020 ) and Bactrocera tryoni (Majumder et al, 2022 ). Both studies using 16S rRNA gene amplicon data sets reported a strong effect of the degree of laboratory adaptation on the structure of the gut bacterial community at each developmental stage.…”
Section: Discussionmentioning
confidence: 99%
“…However, the colonization and production methods that may lead to the production of flies with improved fitness, are indeed very challenging. The laboratory adaptation processes of the strains used under artificial mass rearing have been reported to improve development, survival, and reproduction under a laboratory environment (Liedo et al, 2007 ; Diamantidis et al, 2011 ; Majumder et al, 2022 ), but at the same time, they commonly have detrimental effects on field performance (Liedo et al, 2007 ; Pereira et al, 2007 ; Hernández et al, 2009 ). The culturing of tephritid fruit flies is generally associated with fast development of flies, increase in body size, and survival while some incompatibility with wild flies may evolve in mating behavior and reduced environmental tolerance (Mangan, 1997 ; Miyatake, 1998 ; Briceño and Eberhard, 2002 ; Zygouridis et al, 2014 ; Schutze et al, 2015 ; Pérez et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To decode the functional implications of these gut symbionts, it is necessary to study their distribution. Thus, we have summarized recent metagenomics studies (whole insect and insect gut) of several insect pests which is demonstrated by phylum wise composition of bacteria in Figure 1A ( Yong et al, 2017 ; Tokuda et al, 2018 ; Bozorov et al, 2019 ; Gawande et al, 2019 ; Shah et al, 2020 ; Asimakis et al, 2021 ; Deguenon et al, 2021 ; He et al, 2021 ; Tegtmeier et al, 2021 ; Yu et al, 2021 ; Csorba et al, 2022 ; Li S. et al, 2022 ; Majumder et al, 2022 ; Wang et al, 2022 ). We have noticed with taken examples that Proteobacteria, Firmicutes and Actinobacteria were the most dominant phyla present in the insect gut could be due to their diverse roles in nutrition.…”
Section: Symbiotic Microbes: a Boon For Insectsmentioning
confidence: 99%